2010
DOI: 10.1038/onc.2009.503
|View full text |Cite
|
Sign up to set email alerts
|

High sensitivity to carcinogens in the brain of a mouse model of Alzheimer's disease

Abstract: Cancer and Alzheimer's disease (AD) are commonly found among elderly patients. Chronic inflammation is the characteristic of both diseases. Amyloid-b peptide is the main inducer of inflammation in AD. Moreover, chronic inflammation promotes cancer, suggesting that AD patients may be more prone to develop cancer than nondemented people. To test this hypothesis, we injected the carcinogen 20-methylcholanthrene in the brain of transgenic mice overexpressing the mutant forms of amyloid precursor protein (APP) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 53 publications
1
18
0
3
Order By: Relevance
“…Zhou and Jia [50] demonstrated a p53-mediated G1/S checkpoint dysfunction in lymphocytes from sporadic AD, due to p53 conformational changes that affected its tertiary structure. Furthermore, Serrano et al, [51] demonstrated a significant increase of unfolded p53 in older AD transgenic mice when compared with younger APPswe/PS1A246E animals and wild-type counterparts of the same age. These latter data suggest also a correlation between unfolded p53 and aging.…”
Section: Discussionmentioning
confidence: 96%
“…Zhou and Jia [50] demonstrated a p53-mediated G1/S checkpoint dysfunction in lymphocytes from sporadic AD, due to p53 conformational changes that affected its tertiary structure. Furthermore, Serrano et al, [51] demonstrated a significant increase of unfolded p53 in older AD transgenic mice when compared with younger APPswe/PS1A246E animals and wild-type counterparts of the same age. These latter data suggest also a correlation between unfolded p53 and aging.…”
Section: Discussionmentioning
confidence: 96%
“…However, current evidence seems to point to the existence of direct co-morbidities between brain tumors and CNS diseases 16, 47, 48 . Additionally, a mouse model of AD displays high sensitivity to brain tumors 49 . We propose here that the significant number of genes deregulated in the same direction in both diseases could be an additional argument in favor of direct co-morbidity between AD and GBM.…”
Section: Discussionmentioning
confidence: 99%
“…Such a functional relationship between APP expression and proliferation demonstrates the importance of APP in the pathogenesis of cancer. APP-overexpressing mice are prone to develop brain carcinomas (43). However, the precise mechanism underlying the tumor growth-promoting effect of APP remains to be clarified.…”
Section: Discussionmentioning
confidence: 99%